Attending to the visual aspects of visual storytelling: using art and design concepts to interpret and compose narratives with images. Issue 1 (3rd April 2019) - Williams, Wendy R.
Abstract: Visual storytelling comes in many forms (e.g. films, comics, photographs, commercials) and is used for a range of purposes (e.g. to entertain, inform, persuade). Technological advances are enabling non-specialists to be consumers and producers of these works. Although many people are growing up surrounded by visual works, this does not mean that they carefully attend to images. Education must prepare students to navigate the changing visual landscape. This study, which investigates an undergraduate Visual Narratives course taught in spring 2017 in the United States, focuses on students' uses of art and design elements. A content analysis of 124 course documents shows a wide range of art and design elements at work in students' visual narrative analyses (27 elements) and original compositions (26 elements), with many elements overlapping (21 shared). These results suggest that teaching a wide range of art and design elements can help students acquire a flexible toolkit for reading and composing different kinds of visual texts, expanding their visual literacy. Rather than serving as an end goal, this foundational knowledge offers a focused way of looking that could be combined with other lenses (critical race theory, feminist theory, etc.).